To Determine the Efficacy of Suprachoroidal Triamcinolone Injection for the Treatment of Refractory Diabetic Macular Edema - Ayesha Chandni, Sharfe Rehman Bhatti, Fatima Khawer, Maryam Ijaz, Danish Rafique, Tanveer Ahmed Choudhry, (Pakistan Journal of Medical & Health Sciences, 2023)
Goal: To determine the safety and effectiveness of suprachoroidal triamcinolone injections (SCT) in refractory diabetic macular edema cases. Study Design: An Interventional case series. Place and Duration: In the Ophthalmology department of Allama Iqbal Memorial Teaching Hospital, Sialkot for six-months duration from January 2021 to June 2021 Methods: A total of 40 eyes from patients with type-I or II diabetes who were over the age of 18 years and were included. Inclusion criteria for the study included patients with treatment resistant central Diabetic Macular Edema of at least 320 um or above (as determined by Zeiss Cirrus HD-OCT) and a BCVA of equal to or less than 20/40. The central subfield thickness (CST), BCVA, and intraocular pressure (IOP) were all documented. Patients who had received suprachoroidal triamcinolone (SCTA) were monitored for 3-months and the similar clinical parameters were noted, and the findings were noted. Results: The results showed that 22 (55%) of the 40 patients were female and 18 (45%) were male. The 0.9± 0.22 was the mean log MAR BCVA and 612.89± 195.58 um was the mean pre-injection CST. In the first and third months, the mean post-injection CST was 308.59± 56.75um and 304.89± 54.29um, respectively. After injection at 1 and 3-months, the mean log MAR BCVA was 00.51± 0.3 and 0.36 ±0.20, correspondingly. At the first and third months, the results for pre- and post-injection CST were statistically significant (p value <0.00001). Conclusion: The reduction of refractory diabetic macular edema and improvement of macular thickness on OCT can both be accomplished safely and effectively using CST. Keywords: Central subfield thickness, suprachoroidal triamcinolone, diabetic macular edema.